2013
DOI: 10.1155/2013/378168
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Pesticide Residues in Cannabis Smoke

Abstract: The present study was conducted in order to quantify to what extent cannabis consumers may be exposed to pesticide and other chemical residues through inhaled mainstream cannabis smoke. Three different smoking devices were evaluated in order to provide a generalized data set representative of pesticide exposures possible for medical cannabis users. Three different pesticides, bifenthrin, diazinon, and permethrin, along with the plant growth regulator paclobutrazol, which are readily available to cultivators in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 7 publications
0
56
0
Order By: Relevance
“…This is concerning as this pesticide is not registered with the Environmental Protection Agency (EPA) for use on food crops. Our prior studies have shown that up to 70% of this chemical may be transferred into the smoke stream when present on cannabis (Sullivan et al, 2013). Even when pesticides that are approved for food crops are used there are multiple additional considerations that need to be made for cannabis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is concerning as this pesticide is not registered with the Environmental Protection Agency (EPA) for use on food crops. Our prior studies have shown that up to 70% of this chemical may be transferred into the smoke stream when present on cannabis (Sullivan et al, 2013). Even when pesticides that are approved for food crops are used there are multiple additional considerations that need to be made for cannabis.…”
Section: Discussionmentioning
confidence: 99%
“…Previously described methods for cannabinoid profiling utilizing HPLC-UV were employed (Elzinga et al, 2015). A previously described method utilizing GC-MS in SIM mode was used for pesticide and plant growth regulator residue detection (Sullivan et al, 2013). The following compounds were analyzed for: Bifenthrin, Carbaryl, Diazinon, Fluvalinate, Malathion, Myclobutanil, Paclobutrazol and Permethrin.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Vaporizers are oft en used to heat marijuana to a temperature suffi cient to evaporate cannabinoids but not burn plant material, resulting in limited inhalation of tar and irritants ( 21 ) . Other new inhalation methods, such as water pipes with carbon fi ltration systems, appear to reduce exposure to pesticides present in cultivated marijuana ( 22 ) .…”
Section: Practical Aspects and Consequences Of Medical Marijuana Usementioning
confidence: 99%
“…This is of great concern because this pesticide is not registered by the U.S. Environmental Protection Agency (EPA) for use on food crops. Sullivan et al has previously reported that up to 70% of paclobutrazol is transferred into the smoke stream [12]. Two other pesticides found in the US samples were bifenthrin (a pyrathroid insecticide) and myclobutanil (a systemic fungicide).…”
mentioning
confidence: 97%